2012
DOI: 10.1097/jgp.0b013e31822ccd79
|View full text |Cite
|
Sign up to set email alerts
|

Family Connectedness Moderates the Association Between Living Alone and Suicide Ideation in a Clinical Sample of Adults 50 Years and Older

Abstract: Objective To investigate whether living alone is significantly associated with expression of suicide ideation among mood-disordered mental health patients and whether degree of family connectedness moderates the association between living alone and expression of suicide ideation. Design Cross-sectional survey design. Setting Inpatient and outpatient mental health services in Rochester, New York. Participants 130 mood disordered inpatients and outpatients 50 years or older. Measurements Patients complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 38 publications
0
39
1
1
Order By: Relevance
“…For example, research has shown that older adults at risk for suicide are more likely to have experienced threats to independence (i.e. physical illness and functional decline) (4) and social isolation (5,6,7). Finally, recent research examining distress in older adults accessing aging services has demonstrated high levels of depression and anxiety in this population (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has shown that older adults at risk for suicide are more likely to have experienced threats to independence (i.e. physical illness and functional decline) (4) and social isolation (5,6,7). Finally, recent research examining distress in older adults accessing aging services has demonstrated high levels of depression and anxiety in this population (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Purcell et al (2012) conducted a study with 130 adults aged 50 years and older who suffered from a mood disorder and found that living alone was not associated with suicidal ideation. Results indicated, however, an interaction between living arrangements and family connectedness.…”
mentioning
confidence: 99%
“…Their findings support the literature demonstrating negative associations between aspects of psychopathology and MIL, and support the validity of the GSIS MIL subscale. Although their findings essentially support associations between MIL and a sense of concern for others, they suggest that older adults who struggle with a perceived lack of social support or who perceive themselves to be a burden upon others may struggle to recognize MIL, and may ultimately contemplate ending their lives (Heisel and Flett 2006;Purcell et al 2012). Breitbart and colleagues reported that terminally ill older adults lacking recognition of MIL are at heightened risk for desiring to hasten death (Breitbart et al 2000;McClain et al 2003McClain et al , 2004.…”
Section: Discussionmentioning
confidence: 91%